P-P40 Can trainees safely perform pancreatoduodenectomy? A systematic review, meta-analysis and risk-adjusted analysis of post-operative pancreatic fistula. (16th December 2021) - Pande, Rupaly; Halle-Smith, James; Thorne, Tom; Hodson, James; Roberts, Keith J
Abstract: Background: The complexity of pancreaticoduodenectomy (PD) and fear of morbidity, particularly post-operative pancreatic fistula (POPF), can be a barrier to surgical trainees gaining operative experience.  Objective: to compare the POPF rate following PD by trainees or established surgeons. Methods: A systematic review of the literature was performed using PRISMA guidelines, with differences in POPF rates after PD between trainee-led vs. consultant/attending surgeons pooled using meta-analysis. Variation in rates of POPF was further explored using risk-adjusted outcomes using published risk scores and CUSUM analysis in a retrospective cohort.    Results: Across 14 cohorts included in the meta-analysis, trainees tended towards a lower, but non significant rate of All-POPF (odds ratio [OR]: 0.77, p = 0.45) and clinically relevant (CR)-POPF (OR: 0.69, p = 0.37). However, there was evidence of case selection, with trainees being less likely to operate on patients with a pancreatic duct width <3mm (OR: 0.45, p = 0.05). Similarly, analysis of a retrospective cohort (N = 756 cases) found patients operated by trainees to have significantly lower predicted All-POPF (median: 20 vs. 26%, p < 0.001) and CR-POPF (7 vs. 9%, p = 0.020) rates than consultant/attending surgeons, based on pre-operative risk scores. After adjusting for this on multivariable analysis, the risks of All-POPF (OR: 1.18, p = 0.604) and CR-POPF (OR: 0.85, p = 0.693) remained similar after PD by trainee or consultant/attending surgeons. Conclusions: PD, when performed by trainees, is associated with acceptable outcomes. There is evidence of case selection among patients undergoing surgery by trainees; hence, risk adjustment provides a critical tool for the objective evaluation of performance.